Sedimentos eólicos de grano fino en la Bahía de San Sebastián, Tierra del Fuego, Argentina. - Arche, A.; Vilas, Federico (Journal of Iberian Geology, 2001)
San Sebastian Bay, Argentina, is a large coastal embayment in the macrotidal Atlantic coast of Tierra del Fuego Island. Active sedimentation takes place in wide Instituto de Geología Económica, CSIC-UCM. Facultad de Ciencias Geológicas, Universidad (1) Complutense, 28040 Madrid. Fax: 913944808. Departamento de Xeociencias Mariñas e Ordenacion do Territorio. Facultade do Ciencias. Universidade do (2) Vigo, 36200 Vigo, Pontevedra. Fax:986812556. 159 Alfredo Arche y Federico Vilas intertidal flats and gravel beaches. Strong westerly winds, up to 158 km/h, rework the top of the intertidal sediments separating sand-sized mud pellets that accumulate in sheets of eolian deposits with characteristic trough cross-bedding and rootlet levels. Rainwater percolating though the sediments dissagregate the mud pellets, almost obliterating the primary internal structures of the eolian sediments.